Do the Buildings Really Matter? Czech, Polish and Slovak Museums and Centres of Contemporary Art in Adapted Buildings. (3rd July 2018) - Jagodzińska, Katarzyna
ABSTRACT: This paper discusses the connection between museums and centres of contemporary art operating in adapted buildings, on the one hand, and on the other, the history of the place where the buildings are located. I discuss seven discrete case studies, representing a variety of approaches to buildings and the areas in which they operate, in the Czech Republic, Poland and Slovakia. My analysis of each case study covers four main subject areas: (1) discussions connecting the building's history with its new role; (2) the architectural features and appearance of the building; (3) references3 to the history of the site in the institution's programme and communication; and (4) efforts to build bonds with local communities. In my conclusions, I argue that the identity of the institution may either be rooted in the history of the place presented and discussed in its programme, or be independent of the history of the building but nonetheless connected to the area in which it is located.